Effect of Plasmodium falciparum sulfadoxine-pyrimethamine resistance on the effectiveness of intermittent preventive therapy for malaria in pregnancy in Africa: a systematic review and meta-analysis. - van,Eijk AM; Larsen,DA; Kayentao,K; Koshy,G; Slaughter,DEC; Roper,C; Okell,LC; Desai,M; Gutman,J; Khairallah,C; Rogerson,SJ; Hopkins,Sibley C; et al. (Lancet Infectious Diseases, 2019)
BACKGROUND: Resistance of Plasmodium falciparum to sulfadoxine-pyrimethamine threatens the antimalarial effectiveness of intermittent preventive treatment during pregnancy (IPTp) in sub-Saharan Africa. We aimed to assess the associations between markers of sulfadoxine-pyrimethamine resistance in P falciparum and the effectiveness of sulfadoxine-pyrimethamine IPTp for malaria-associated outcomes. METHODS: For this systematic review and meta-analysis, we searched databases (from Jan 1, 1990 to March 1, 2018) for clinical studies (aggregated data) or surveys (individual participant data) that reported data on low birthweight (primary outcome) and malaria by sulfadoxine-pyrimethamine IPTp dose, and for studies that reported on molecular markers of sulfadoxine-pyrimethamine resistance. Studies that involved only HIV-infected women or combined interventions were excluded. We did a random-effects meta-analysis (clinical studies) or multivariate log-binomial regression (surveys) to obtain summarised dose-response data (relative risk reduction [RRR]) and multivariate meta-regression to explore the modifying effects of sulfadoxine-pyrimethamine resistance (as indicated by Ala437Gly, Lys540Glu, and Ala581Gly substitutions in the dhps gene). This study is registered with PROSPERO, number 42016035540. FINDINGS: Of 1097 records screened, 57 studies were included in the aggregated-data meta-analysis (including 59457 births). The RRR for low birthweight declined with increasing prevalence of dhps Lys540Glu (ptrend=0·0060) but not Ala437Gly (ptrend=0·35). The RRR was 7% (95% CI 0 to 13) in areas of high resistance to sulfadoxine-pyrimethamine (Lys540Glu ≥90% in east and southern Africa; n=11), 21% (14 to 29) in moderate-resistance areas (Ala437Gly ≥90% [central and west Africa], or Lys540Glu ≥30% to <90% [east and southern Africa]; n=16), and 27% (21 to 33) in low-resistance areas (Ala437Gly <90% [central and west Africa], or Lys540Glu <30% [east and